Effect of polypropylene fibers on thermogravimetric properties of self-compacting concrete at elevated temperatures - Al Qadi A.N.S.; Bin Mustapha K.N.; Naganathan S.; Al-Kadi Q.N.S. (2023)
In this study, the effect of polypropylene (PP) fibers on thermogravimetric parameters of self-compacting concrete (SCC) containing indigenous materials was investigated experimentally and statistically. The mixes containing cement, water, fly ash, fine aggregate, coarse aggregate, and super plasticizer, with the addition of PP fibers (0%, 0.05%, 0.1%, and 0.15%) by volume of the mixtures, were prepared. The physical properties of SCC were determined at elevated temperatures (200, 400, and 600 C) after cooling in the laboratory. Regression models were developed to determine the responses, and the optimum amount of 0.05% PP fibers by volume was measured. Copyright 2012 John Wiley & Sons, Ltd. Copyright 2012 John Wiley & Sons, Ltd.